Staying Awake and Aware: The Importance of Sleep in Psychiatric Nursing Practice. (2nd November 2017) - Tobin, Thomas; Tobin, Mary L.
ABSTRACT: Given that approximately 70 million Americans suffer from sleep–wake disorders and their under-recognized role in practice, psychiatric nurses may see, or may be already seeing, patients with undiagnosed sleep disorders. Assessment of sleep–wake disorders can and should be a part of psychiatric nursing education and practice. Many practicing clinicians lack formal training regarding sleep–wake issues and treatment. Even as sleep disturbances are common concerns among psychiatric populations, sleep–wake issues may go unrecognized. The article presents a stylized progression of care to enable clinicians to identify, address, and treat underlying sleep–wake disorders in psychiatric settings. The article recommends instituting screening procedures for sleep–wake issues and follow-up assessments, particularly overnight pulse oximetry and polysomnograms. Just as clinicians already screen for physical conditions that would affect psychiatric care, practitioners can evaluate patients for potential sleep–wake disorders as part of their existing practice and intake procedures. Further, the piece details implications for psychopharmacology as well as evidence from clinical practice. Psychiatric nurses should stay awake to the importance of sleep medicine and aware of how sleep–wake disorders can affect psychiatric populations.